Combined administration of antibiotics increases the incidence of antibiotic-associated diarrhea in critically ill patients - Ma H; Zhang L; Zhang Y; Liu Y; He Y; Guo L (Infection and Drug Resistance, 2019)
Hongye Ma,1 Lei Zhang,1 Yanshu Zhang,1 Yu Liu,1 Yingli He,2 Litao Guo11Department of Critical Care Medicine, The First Affiliated Hospital of Xi’an Jiaotong University, Xi’an, People’s Republic of China; 2Department of Infectious Diseases, The First Affiliated Hospital of Xi’an Jiaotong University, Xi’an, People’s Republic of ChinaBackground: The widespread use of antibiotics has resulted in a high incidence of antibiotic-associated diarrhea (AAD); moreover, the AAD-associated mortality rates have also increased. The effect of combined antibiotic administration on AAD in critically ill patients was analyzed to assist in antibiotic selection for AAD prevention.Methods: Clinical data of patients hospitalized were retrospectively analyzed. Patients were either assigned to the combined-use group (CG) or the monotherapy group (MG). Age, sex, albumin levels, proton pump inhibitors, the type antibiotics, occurrence of AAD were collected. All relevant data were analyzed using SPSS version 18.0 (IBM Inc., Armonk, NY, USA), and significance was set at P<0.05.Measurements and main results: Overall, 277 patients were enrolled (CG, n=143; MG, n=134). The incidence of AAD was significantly different between the groups (44.06% vs 17.16%, P<0.001). Combined use of three or more antibiotics, other antibiotics combined with antifungals antibiotics increases the incidence of AAD (P<0.05). Duration of proton pump inhibitor therapy (odds ratio [OR] 1.142, 95% confidence interval [CI] 1.048–1.244, P=0.002), antifungal antibiotic administration (OR 3.189, 95% CI 1.314–7.740, P=0.010), and beta-lactam plus enzyme inhibitor antibiotic administration (OR 3.072, 95% CI 1.309–7.205, P=0.010) were associated with AAD in critically ill patients receiving combined antibiotics therapy. The mean duration of intensive care unit admission was longer among patients with AAD compared with patients without AAD (19.70±12.16 vs 12.29±8.06 days, P<0.001), with no significant difference in intensive care unit-related mortality rates.Conclusion: Combined administration of antibiotics, especially beta-lactam plus enzyme inhibitors and antifungals, may increase the incidence of AAD in critically ill patients.Keywords: diarrhea, pseudomembranous colitis, intensive care units, antibiotics